Etika Bisnis Islam Dalam Era Bisnis Kekianian (Studi Kasus Kedai Kopi Diskuupi Surabaya) - Maydiana, Sherin; Cahyono, Hendry (Jurnal Ekonomika dan Bisnis Islam, 2020)
The tren of consuming coffee among young people today has great potential to increase the amount of coffee consumption in Indonesia. With the proliferation of coffee shops in various cities is proof that coffee lovers are increasing. One of the coffee-based businesses that are in demand today is the current coffee shop. As business people, especially Muslim business people, in conducting their business they should apply business ethics as a driever of competitive behavior so that they are by existing norms and by those stipulated in the Quran, Hadith, and other Islamic sources. This research uses descriptive qualitative case study approach to examine a case that occurs in a certain place and time. The result showed that based on the results of interviews conducted with two sources and compared in-depth discussions with theories and previous studies, Diskuupi only applied the principle of balance, free will, and truth: virtue and honesty, and responsibility.